2000
DOI: 10.1161/01.atv.20.4.957
|View full text |Cite
|
Sign up to set email alerts
|

Apoptosis and Regulation of Bax and Bcl-X Proteins During Human Neonatal Vascular Remodeling

Abstract: Abstract-To verify that apoptosis is one of the possible mechanisms of neonatal vascular remodeling during the transition from fetal to neonatal circulation, we assayed for apoptosis and evaluated the expression of apoptosis-regulatory proteins in umbilical vessel versus ascending aorta, ductus arteriosus (DA) versus adjacent pulmonary artery and aorta, or aorta versus its branching arteries. Twenty-two umbilical cords (UCs), 6 DAs with adjacent aortas and pulmonary arteries, and 4 aortic arches with their bra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
23
0

Year Published

2000
2000
2009
2009

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 37 publications
1
23
0
Order By: Relevance
“…Coincident upregulation of proapoptotic members of the Bcl2 family (Bax and the short form of BclX) was observed in umbilical arteries. 84 Importantly, Kim et al 84 also observed apoptosis near large arterial branch sites postpartum, a finding consistent with a role for cell death in remodeling of arterial bifurcations during perinatal development.…”
Section: Hemodynamics and Apoptosismentioning
confidence: 81%
See 2 more Smart Citations
“…Coincident upregulation of proapoptotic members of the Bcl2 family (Bax and the short form of BclX) was observed in umbilical arteries. 84 Importantly, Kim et al 84 also observed apoptosis near large arterial branch sites postpartum, a finding consistent with a role for cell death in remodeling of arterial bifurcations during perinatal development.…”
Section: Hemodynamics and Apoptosismentioning
confidence: 81%
“…Not surprisingly, extensive postnatal apoptosis occurs in vessels that regress after birth, ie, the umbilical arteries 66,84 and ductus arteriosus. 84 The extent to which death of these highly specialized cells is linked to hemodynamics is unknown.…”
Section: Hemodynamics and Apoptosismentioning
confidence: 99%
See 1 more Smart Citation
“…An acute increase in oxygen tension causes perinatal pulmonary vasodilation (3,26), even while it results in constriction of the DA (1,5). Initial closure of the DA in response to an increase in PO 2 is caused by vessel constriction (14), whereas long-term closure is accomplished through cell migration, apoptosis (25), and cell proliferation (4,15,18).…”
mentioning
confidence: 99%
“…Accordingly, apoptosis seems to be vital during the transition from intra-to extrauterine life, since the former constitutes an immune privilege for the fetus [33] indicated by the special immunologic characteristics of umbilical cord blood cells [34] . In this respect, apoptosis is reportedly diminished in umbilical cord blood neutrophils compared to adult cells [34] .…”
Section: Discussionmentioning
confidence: 99%